The Euro Interbank Repo Market - Mancini, Loriano; Ranaldo, Angelo; Wrampelmeyer, Jan (Review of Financial Studies, 2016)
The search for a market design that ensures stable bank funding is at the top of regulators' policy agenda. This paper empirically shows that the central counterparty (CCP)-based euro interbank repo market features this stability. Using a unique and comprehensive data set, we show that the market is resilient during crisis episodes and may even act as a shock absorber, in the sense that repo lending increases with risk, while spreads, maturities, and haircuts remain stable. Our comparison across different repo markets shows that anonymous CCP-based trading, safe collateral, and the absence of an unwind mechanism are the key characteristics to ensure market resilience.